The Impact of Inclusion on Organizational Citizenship Behavior - El Hajj, Joey (2022)
This study aims to examine the relationships between inclusion, employee well-being, and organizational citizenship behavior. It also aims at investigating the role of employee well-being as a mediator. Drawing on the Social Identity theory and Social Exchange theory, this study attempts to examine the importance of inclusion and employee well-being in initiating organizational citizenship behaviors at the workplace. A total of 203 completed questionnaires were obtained and analyzed. The results of this study provided support to the hypothesized relationships. Results indicated that the direct relationships were supported between Inclusion, Employee well-being and Organizational Citizenship Behavior. In addition, the results have also provided support to the mediating role of employee well-being. Finally, the findings of this study provide theoretical and practical implications taking into consideration the limitations.